Reasons patients leave their nearest healthcare service to attend Karen Park Clinic, Pretoria North - Agnes T. Masango- Makgobela; Indiran Govender; John V. Ndimande (AOSIS, 2013)
Background: Many patients move from one healthcare provider or facility to another, disturbing the continuity that enhances holistic patient care. Objectives: To investigate the reasons given by patients for attending Karen Park Clinic rather than the clinic nearest to their homes. Methods: A cross-sectional descriptive study was conducted during 2010. Three hundred and fifty patients attending Karen Park Clinic were given questionnaires to complete, with the following variables: place of residence; previous attendance at the clinic nearest their home; services available at their nearest clinic; and their willingness to attend their nearest clinic in future. Results: Respondents were from Soshanguve (153; 43.7%), Mabopane (92; 26.3%), Garankuwa (29; 8.3%) and Hebron (20; 5.7%) and most were women (271; 77.4%) aged 26-45 (177; 50.6%). Eighty per cent (281) of the patients had visited their nearest clinic previously and 54 of these (19.2%) said they would not return. The reasons for this were: long waiting time (88; 25.1%); long queues (84; 24%); rude staff (60; 17%); and no medication (39; 11.1%). Conclusion: The majority of patients who had attended their nearest clinic were adamant that they would not return. It is necessary to reduce waiting times, thus reducing long queues. This can be achieved by having adequate, satisfied healthcare providers to render a quality service and by organising training for management. Patients can thus be redirected to their nearest clinic and the health centre's capacity can be increased by procuring adequate drugs. There is a need to follow up on patients' complaints about staff attitudes.